A Simple and Rapid High-Performance Liquid Chromatography—Photodiode Array Method for Quantitation of Triacetin Contents From 30 Batches Produced in China. (20th October 2020) - Li, Ran; Pan, Xi; Wang, Hao; Guo, Guoning; Huang, Long; Wei, Min; Ma, Yuanren; Zhang, Jinyan; Hao, Ji; Song, Xuyan; Yang, Xinzhou
Abstract: In our present study, the standard chemicals of triacetin were purified by reverse-phase and normal-phase semi-preparative high-performance liquid chromatography (HPLC), and 1 H NMR and 13 C NMR were employed to determine the purity and structure of triacetin. Moreover, a simple and rapid HPLC-photodiode array (PDA) method was developed to determine the contents of triacetin in 30 batches from different suppliers. The chromatographic separation was performed on a Phenomenex Gemini-NX C18 column (250 × 4.6 mm, 5 μm) using a gradient elution system of water and acetonitrile (contained 0.1% of formic acid) solution with a flow rate of 1.0 mL/min at 30°C at 210 nm. Sample preparation method is rapid and energy efficient, and the obtained sample have a good purity. Validation shows good specificity, linearity ( R 2 = 0.9995), precision, stability, repeatability (% RSD < 2.80) and the average recovery (99.72%) of triacetin. The content of triacetin in most samples is concentrated in 94–97%. This developed approach is simple, rapid, accurate and can be used to quickly determine the purity and the content of triacetin in plasticizers and filter plugs.